1992
DOI: 10.1111/j.1528-1157.1992.tb02336.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Quantitative Autoradiography of [3H]‐L‐Deprenyl and [3H]‐PK 11195 Binding Sites in Human Epileptic Hippocampus

Abstract: Distribution of the enzyme monoamine oxidase B (MAO-B) and the peripheral benzodiazepine binding site (omega 3 site) was studied by quantitative autoradiography using [3H]L-deprenyl and [3H]PK 11195, two tentative glial markers, as ligands. Sclerotic hippocampus from seven patients who had had anterotemporal lobe resection because of intractable complex partial epilepsy were investigated and compared with postmortem hippocampus from three nonepileptic controls. A significantly higher degree of L-deprenyl and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…These results are in line with autoradiographic studies showing a decrease of 3H-Ro 15-1788 that correlated with neuronal loss in resected tissue of patients with temporal lobe epilepsy.22 23 Conclusions This study illustrates that single methods as part of non-invasive presurgical evaluation may have limited localising capacity. Convergence of the results of different methods can improve the ability to indicate the localisation of the focus with more precision.…”
Section: Comparison Between Pet and Spectsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in line with autoradiographic studies showing a decrease of 3H-Ro 15-1788 that correlated with neuronal loss in resected tissue of patients with temporal lobe epilepsy.22 23 Conclusions This study illustrates that single methods as part of non-invasive presurgical evaluation may have limited localising capacity. Convergence of the results of different methods can improve the ability to indicate the localisation of the focus with more precision.…”
Section: Comparison Between Pet and Spectsupporting
confidence: 83%
“…Extratemporal abnormalities seen in three patients (6,8,23), were described as white matter abnormalities in all the patients concerned, probably without specific relevance. In one patient (6) abnormalities of white matter were combined with medial temporal sclerosis.…”
Section: Mrimentioning
confidence: 92%
See 1 more Smart Citation
“…Recent evidence in animal models of epileptogenesis and in patients with pharmacoresistant seizures have demonstrated that both the extent and regional pattern of glial cell activation can be imaged non-invasively: astrocyte activation can be monitored by measuring specific metabolites using proton magnetic resonance spectroscopy ( 1 H-MRS) [26] or monoamine oxidase(MAO)-B by positron emission tomography (PET) [27][28][29], while microglia/macrophage activation can be measured by PET imaging of translocator protein 18 (TSPO) [30][31][32]. In particular, 1 H-MRS is an in vivo imaging technique which allows area-specific detection and quantification of myo-inositol (mIns), a sugar alcohol found predominantly in astrocytes [26], which represents a quantifiable indicator of reactive astrogliosis [33,34].…”
Section: Non-invasive Imaging Of Brain Astrocytesmentioning
confidence: 99%
“…Available data suggest that there is endogenous opioid release during the ictal phase, resulting in reduced receptor availability and reduced tracer binding, followed by low levels of endogenous opioids, resulting in increased receptor availability and therefore increased tracer binding. Similarly, the level of monoamine oxidase B has been found to be both high (58) and low (59) in temporal lobe epilepsy. Although significantly reduced dopamine receptor binding has been reported in the epileptogenic temporal lobe in temporal lobe epilepsy (60), no binding alterations were found with PET using 11 C-verapamil, a p-glycoprotein substrate (61).…”
Section: Temporal and Extratemporal Lobe Epilepsy Pet Imagingmentioning
confidence: 99%